Regulation of Tim-3 function by binding to phosphatidylserine. Issue 22 (26th November 2021) - Kane, Lawrence P.
Abstract : Tim-3 is a transmembrane protein that is highly expressed on subsets of chronically stimulated CD4+ helper and CD8+ cytotoxic T cells, with more transient expression during acute activation and infection. Tim-3 is also constitutively expressed by multiple types of myeloid cells. Like other TIM family members, Tim-3 can bind to phosphatidylserine displayed by apoptotic cells, and this interaction has been shown to mediate uptake of such cells by dendritic cells and cross-presentation of antigens to CD8+ T cells. In contrast, how the recognition of PS by Tim-3 might regulate the function of Tim-3+ T cells is not known. In their recent paper, Lemmon and colleagues demonstrate for the first time that recognition of PS by Tim-3 leads to enhanced T cell activation.